Analysis of the volume of silted sediments and the urbanization rate in urban river basins; a case study of the Mãe d’Água Reservoir - Fernandes, Felippe; Poleto, Cristiano (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2022)
The Mãe d`Água reservoir is the mouth of four streams, corresponding to an area of 352 ha and is located in the Vale Campus of the Federal University of Rio Grande do Sul. The study area is currently predominantly characterized by a residential occupation, with environmental liabilities coming from diffuse sources. The application of the methodology for computational modeling in the Mãe d'Água reservoir, inferring about the useful volume of the project in 1962, useful volume in 2014, and the silting volume was developed with the aid of the following software: AutoCAD 2018, AutoCAD Civil 3D 2018, and Google Earth which specialize in the field of geoprocessing and guidelines for the calculations that use as base the data regarding the survey and processing of field data. Two types of remote sensing products were used to evaluate the evolution of urbanization in the study area: aerial photographs and satellite images which were integrated in a geographic database. Through the results, it was possible to verify that the silting volume occupies approximately 44% of the useful volume of the reservoir, the urbanization rate has growth trends, and, 88.42% of the river basin was urbanized in 2014. Thus, it represents a spatial distribution and establishes correlations between sedimentation studies over the last five decades.